2004
DOI: 10.1289/ehp.6451
|View full text |Cite
|
Sign up to set email alerts
|

Cause-specific mortality and the extended effects of particulate pollution and temperature exposure.

Abstract: Air pollution exposure studies in the past decade have focused on acute (days) or long-term (years) effects. We present an analysis of medium-term (weeks to months) exposure effects of particulate pollution and temperature. We assessed the associations of particulate pollution (black smoke) and temperature with age-standardized daily mortality rates over 17 years in Dublin, Ireland, using a polynomial distributed lag model of both temperature and particulate air pollution simultaneously through 40 days after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
138
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 32 publications
17
138
1
6
Order By: Relevance
“…31,212 Studies using distributed lag models to evaluate associations from 5 to Յ60 days after exposure have been conducted using data from 10 U.S. cities, 213,214 European cities from the APHEA-2 project, 215,216 and Dublin. 217 In all of these analyses, the net PM-mortality effect was larger when time scales longer than a few days were used.…”
Section: Daily Time Series Studies With Longer Time Scales or Extendementioning
confidence: 99%
“…31,212 Studies using distributed lag models to evaluate associations from 5 to Յ60 days after exposure have been conducted using data from 10 U.S. cities, 213,214 European cities from the APHEA-2 project, 215,216 and Dublin. 217 In all of these analyses, the net PM-mortality effect was larger when time scales longer than a few days were used.…”
Section: Daily Time Series Studies With Longer Time Scales or Extendementioning
confidence: 99%
“…However, longitudinal models can incorporate other exposure measures, such as particular exposure lags, cumulative exposure, or different exposure components (see Section 4.1). Distributed lag exposure models can also be used (Schwartz 2000;Diggle, Heagerty, Liang, and Zeger 2002;Goodman, Dockery, and Clancy 2003). These models allow the health effects of air pollution to extend over time.…”
Section: Hosted By the Berkeley Electronic Pressmentioning
confidence: 99%
“…Exposure to common urban air pollutants has been linked to a wide range of adverse health outcomes including respiratory and cardiovascular diseases, asthma exacerbation, reduced lung function and premature death (U.S. EPA, 2006(U.S. EPA, , 2009. Over the past decade, many epidemiologic studies have demonstrated positive associations between air pollution and mortality (Levy et al, 2000;Goodman et al, 2004;Pope et al, 2004;Schwartz, 2004;Analitis et al, 2006). But, many questions regarding the effects of air pollution remain unanswered and overall the effects of air pollution have not been fully quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies of air pollution have used time-series analysis to relate daily asthma rates to daily air pollution levels for short-term associations between air pollution and health. A substantial number of epidemiological studies reported associations between mortality/morbidity with air pollution levels (Rosas et al, 1998;Dales et al, 2000;Levy et al, 2000;Chen et al, 2004;Goodman et al, 2004;Pope et al, 2004;Schwartz, 2004;Chang et al, 2005;Analitis et al, 2006;Dominici et al, 2006;Hinwood et al, 2006;Yang et al, 2007;Yang, 2008;Halonen et al, 2008;Chiu et al, 2009;Halonen et al, 2009;Belleudi, 2010;Hsieh et al, 2010;Gorai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%